Mathematics
         
语言:中文    Language:English
On line Solution of Monovariate Equation:
    Input any unary equation directly, and then click the "Next" button to obtain the solution of the equation.
    It supports equations that contain mathematical functions.
    Current location:Equations > Monovariate Equation > The history of univariate equation calculation > Answer

    Overview: 1 questions will be solved this time.Among them
           ☆1 equations

[ 1/1 Equation]
    Work: Find the solution of equation (604.8-237.05)*(1-x)*(1%+6%-6%) = 0 .
    Question type: Equation
    Solution:Original question:
     (
3024
5
4741
20
)(1 x )(
1
100
+
6
100
6
100
) = 0
    Remove the bracket on the left of the equation:
     Left side of the equation =
3024
5
(1 x )(
1
100
+
6
100
6
100
)
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
3024
5
× 1(
1
100
+
6
100
6
100
)
3024
5
x (
1
100
+
6
100
6
100
)
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
3024
5
(
1
100
+
6
100
6
100
)
3024
5
x (
1
100
+
6
100
6
100
)
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
3024
5
×
1
100
+
3024
5
×
6
100
3024
5
×
6
100
3024
5
x (
1
100
+
6
100
6
100
)
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
756
125
+
4536
125
4536
125
3024
5
x (
1
100
+
6
100
6
100
)
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
756
125
3024
5
x (
1
100
+
6
100
6
100
)
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
756
125
3024
5
x ×
1
100
3024
5
x ×
6
100
+
3024
5
x ×
6
100
4741
20
(1 x )
                                             =
756
125
756
125
x
4536
125
x +
4536
125
x
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
756
125
756
125
x
4741
20
(1 x )(
1
100
+
6
100
6
100
)
                                             =
756
125
756
125
x
4741
20
× 1(
1
100
+
6
100
6
100
) +
4741
20
x (
1
100
+
6
100
6
100
)
                                             =
756
125
756
125
x
4741
20
(
1
100
+
6
100
6
100
) +
4741
20
x (
1
100
+
6
100
6
100
)
                                             =
756
125
756
125
x
4741
20
×
1
100
4741
20
×
6
100
+
4741
20
×
6
100
+
4741
20
x (
1
100
+
6
100
6
100
)
                                             =
756
125
756
125
x
4741
2000
14223
1000
+
14223
1000
+
4741
20
x (
1
100
+
6
100
6
100
)
                                             =
1471
400
756
125
x +
4741
20
x (
1
100
+
6
100
6
100
)
                                             =
1471
400
756
125
x +
4741
20
x ×
1
100
+
4741
20
x ×
6
100
4741
20
x ×
6
100
                                             =
1471
400
756
125
x +
4741
2000
x +
14223
1000
x
14223
1000
x
                                             =
1471
400
1471
400
x
    The equation is transformed into :
     
1471
400
1471
400
x = 0

    Transposition :
      -
1471
400
x = 0
1471
400

    Combine the items on the right of the equation:
      -
1471
400
x = -
1471
400

    By shifting the terms and changing the symbols on toth sides of the equation, we obtain :
     
1471
400
=
1471
400
x

    If the left side of the equation is equal to the right side, then the right side must also be equal to the left side, that is :
     
1471
400
x =
1471
400

    The coefficient of the unknown number is reduced to 1 :
      x =
1471
400
÷
1471
400
        =
1471
400
×
400
1471
        = 1471 ×
1
1471

    We obtained :
      x =
1471
1471
    This is the solution of the equation.

    Convert the result to decimal form :
      x = 1



Your problem has not been solved here? Please go to the Hot Problems section!





  New addition:Lenders ToolBox module(Specific location:Math OP > Lenders ToolBox ),welcome。